Sexual assault in context : [teaching college men about gender] - Kilmartin, Christopher (L. Erlbaum, 2005)
Most North American colleges have programs that help students understand the harm done to victims of sexual violence and, if prosecuted, the potential consequences of their perpetrators. However, only a few programs also address those aspects of masculine culture that surround sexual assault. Sexual Assault in Context addresses the undesirable aspects of masculine culture that sustains the violation of women and girls. It examines several typically overlooked patterns of behavior that provide the basis for sexual assault and provides an overview of masculine psychological development as.